Pulmonary Congestion at Rest and Abnormal Ventilation During Exercise in Chronic Systolic Heart Failure. Issue 5 (May 2015) - Malfatto, Gabriella; Caravita, Sergio; Giglio, Alessia; Rossi, Jessica; Perego, Giovanni B.; Facchini, Mario; Parati, Gianfranco
Abstract : Background: In patients with chronic heart failure, abnormal ventilation at cardiopulmonary testing (expressed by minute ventilation‐to‐carbon dioxide production, or VE/VCO2 slope, and resting end‐tidal CO2 pressure) may derive either from abnormal autonomic or chemoreflex regulation or from lung dysfunction induced by pulmonary congestion. The latter hypothesis is supported by measurement of pulmonary capillary wedge pressure, which cannot be obtained routinely but may be estimated noninvasively by measuring transthoracic conductance (thoracic fluid content 1/kΩ) with impedance cardiography. Methods and Results: Preliminarily, in 9 patients undergoing invasive hemodynamics during cardiopulmonary testing, we demonstrated a significant relationship between VE/VCO2 slope and resting end‐tidal CO2 pressure with baseline and peak pulmonary capillary wedge pressure. Later, noninvasive hemodynamic evaluation by impedance cardiography was performed before cardiopulmonary testing in 190 patients with chronic systolic heart failure and normal lung function (aged 67±3 years, 71% with ischemia, ejection fraction 32±7%, 69% with implantable cardioverter‐defibrillator or cardiac resynchronization therapy). In this group, we determined the relationship between abnormal ventilation (VE/VCO2 slope and resting end‐tidal CO2 pressure) and transthoracic conductance. In the whole population, thoracic fluid content values were significantly related to VE/VCO2 slope ( R =0.63, P <0.0001) and to resting end‐tidal CO2 pressure ( R =−0.44, P <0.001). Conclusions: In patients with chronic heart failure, abnormal ventilation during exercise may be related in part to pulmonary congestion, as detected by resting baseline impedance cardiography.